A life cycle assessment of the Brazilian coal used for electric power generation. (1st April 2015) - Restrepo, Álvaro; Bazzo, Edson; Miyake, Raphael
Abstract: This paper presents the first results concerning a life cycle assessment of the energetic coal obtained from a southern Brazil underground mine, through the rooms and pillars technique, and used for electric power generation. The main purpose was to identify, according to the technology in question, the environmental impacts associated with the production of 1 kg of energetic coal. Two methods of assessment were considered: the Eco-indicator 99 analyzing five environmental categories: carcinogens, respiratory inorganics, ecotoxicity, acidification and land use, and the Intergovernmental Panel on Climate Change, focusing in global warming category over 100 years. The life cycle inventory was obtained from data collected in situ during coal mining and its beneficiation process. Short and long term scenarios were analyzed. In case of long term, due to the highest contribution of tailings, the weighting showed that the carcinogens category was the most representative, followed by respiratory inorganics, land use and ecotoxicity categories. For short term, the respiratory inorganics was found as the most representative category, with important contributions of explosives, electricity and diesel consumption. For both scenarios, the global warming potential index showed 0.0856 kg of CO2-eq per kg of energetic coal, which is a low value when compared with reported values for similar processes. Highlights: First life cycle assessment of the energetic coal mined from a southern Brazil. Results relate to an underground mining coal through the room and pillar technique. LCI obtained from real data collected in situ during energetic coal mining process. Global warming potential index showed 0.0856 kg of CO2-eq per kg of energetic coal. Carcinogens category was the most representative strongly linked to the tailings.